High-performing electrolyte-supported symmetrical solid oxide electrolysis cells operating under steam electrolysis and co-electrolysis modes. (21st May 2020) - Bernadet, Lucile; Moncasi, Carlos; Torrell, Marc; Tarancón, Albert
Abstract: Symmetrical solid oxide cells (s-SOC) present several advantages compared to typical configuration, as a reduction of sintering steps or a better thermomechanical compatibility between the electrodes and the electrolyte. Different mixed ionic-electronic conductors (MIEC) have been reported as suitable candidates for symmetrical configuration, allowing operations under steam electrolysis (SOEC) or co-electrolysis (co-SOEC) without the use of reducing safe gas (typically employed in SoA nickel based cells). In the present study, Sr2 Fe1.5 Mo0.5 O6−δ (SFM) electrodes are deposited on both sides of YbScSZ tapes previously coated with a Ce1-x Gdx O1.9 (GDC) barrier layer grown by PLD. Electrode sintering temperature is optimized and fixed at 1200 °C by means of electrochemical impedance spectroscopy (EIS) measurements in symmetrical atmosphere. The cell is then characterized at 900 °C in SOEC and co-SOEC modes without the use of any safe gas obtaining high current densities of 1.4 and 1.1 A cm −2 at 1.3 V respectively. Short-term reversibility is finally proven by switching the gas atmosphere between the cathode and anode sides while keeping the electrolysis conditions. Similar performances are obtained in both configurations. Highlights: Symmetrical SOC made with SFM deposited on YbScSZ electrolytes tapes. Improved GDC PLD barrier layer. No need of safe gas at the fuel electrode. High performance of symmetric cells in SOEC and co-SOEC. Cell reversibility proven by exchanging gas atmosphere between anode and cathode.